1988
DOI: 10.1271/bbb1961.52.2429
|View full text |Cite
|
Sign up to set email alerts
|

Screening of anaerobic bacteria with the ability to decolorize molasses melanoidin.

Abstract: The screening of facultative anaerobes with melanoidin-decolorizing activity (MDA)was performed, and some strains were isolated from stored waste water of an alcohol fermentation involving molasses. One of them, strain W-NS,showed high and stable MDA,and was identical with Lactobacillus hilgardii. The decolorization yield of this strain under the optimal conditions was only 28%, however, it was improved to 40% by immobilization of cells within Ca-alginate gel. Unlike Basidiomycetes and Ascomycetes, this strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several fungi have been investigated for their ability to remove colour and COD (Table 5) (Satyawali and Balakrishnan 2008). Ohmomo et al (1988) concluded that the decolourization of melanoidins is due to two decomposition mechanisms. In the first one, melanoidins with lower molecular weight are attacked and in the second one, those with a high molecular weight are attacked.…”
Section: Bacterialmentioning
confidence: 99%
“…Several fungi have been investigated for their ability to remove colour and COD (Table 5) (Satyawali and Balakrishnan 2008). Ohmomo et al (1988) concluded that the decolourization of melanoidins is due to two decomposition mechanisms. In the first one, melanoidins with lower molecular weight are attacked and in the second one, those with a high molecular weight are attacked.…”
Section: Bacterialmentioning
confidence: 99%
“…There are various fungi, algae and facultative bacteria capable of melanoidin decolorizing activity (MDA). A variety of facultative anaerobes exhibiting MDA have been identified which can remove approximately a quarter of melanoid present (Ohmomo et al, 1988). This would explain the work of Dwyer's group (2008), and later Higgins" team (2017) who demonstrated a reduction in various parameters associated with refractory components following digestion.…”
Section: Bacterial Decompositionmentioning
confidence: 99%
“…It was found that color removal could be improved by fortuitous metabolism by the addition of 1% glucose as a supplementary carbon source (Kumar & Chandra, 2006). The microbial decolorization of melanoidins is twofold, with certain organisms targeting smaller molecular weight melanoidins (such as W-NS strain) and others specializing against larger molecular weight melanoidins, such as Basidiomycetes and Ascomycetes (Ohmomo et al, 1988). In all instances, supplementation with either nitrogen or carbon source is almost always necessary because the microbial species are not able to utilize the refractory material as the sole carbon source.…”
Section: Bacterial Decompositionmentioning
confidence: 99%